Long term outcomes of Hospital-Identified Clostridium Difficile Infection (HICDI): A retrospective cohort analysis of adult patients in a teaching hospital - Samarasimha R Pandhem; David Michael; Manoj Y Singh (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Objectives: To study long term outcomes of HICDI.  Design, settings and participants: Retrospective cohort study of adult patients diagnosed with HICDI during their admission to a tertiary teaching hospital between January 1st 2012 and December 31st 2016.  Main outcomes: Primary aim was to study two-year mortality outcome and it's predictors in HICDI patients. Secondary outcomes were to identify characteristics of HICDI and predictors of time to resolution of infection.  Results: A total of 819 adult HICDI episodes were identified. 544 episodes occurring in 466 patients were included in final analysis. Single CDI episodes occurred in 409 patients, 45 patients had 2 episodes and 12 patients had greater than 2 episodes. Two-year all-cause mortality was 33% (152/409) in single CDI episodes and 61.4% (35/57) for those with more than one CDI episode. Of the 466 patients, the in-hospital all-cause mortality directly attributed to CDI was 14 patients (3%).  Risk factors predicting long-term mortality were, chemotherapy (AHR(adjusted hazard ratio)2.7; 95% CI 1.90-3.81;p=0.01), low albumin(AHR 2.44; 95% CI 1.83-3.47; p=0.01), ICU admission(AHR 2.09, 95% CI 1.44-3.03; p=0.01) high WBC count (AHR 1.78,CI 1.28-2.30; p=0.01), multiple CDIs (AHR 1.24,95% CI 1.09-1.39; p=0.01) and age (AHR:1.04;95%CI:1.03-1.05;p=0.01). Most common type of HICDI was Hospital -Acquired CDI (HA-CDI) (55.8 %; n=260). Antibiotic usage before developing CDI significantly delayed the time to resolution of infection (AIRR: 1.35; 95% CI 1.06-1.71; p=0.01). In 1/3rd (n=180) of HICDI episodes, patients were discharged before resolution of diarrhoea. Majority of HICDI episodes (n=371) were treated with metronidazole. Conclusion: HICDI was associated with significant long term mortality and morbidity. Mortality increased with more than one CDI infection. Antibiotic usage before developing CDI significantly delayed the time to resolution of infection.